2021
DOI: 10.1177/0192513x21999691
|View full text |Cite
|
Sign up to set email alerts
|

Parenthood Desire in Italian Homosexual Couples

Abstract: Many Italian gay and lesbian individuals have the desire to become parents, despite the fact that they still face barriers due to the low acceptance of same-sex parenthood. This study investigates the desire and motivation of same-sex couples to have children. The sample consists of 31 same-sex couples (17 lesbian couples and 14 gay male couples) and 31 heterosexual couples. All the participants were childless at the time of the study and had been involved in their current relationship for at least two years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Regarding motives for parenthood, research findings in the Italian LG population are mixed. While some studies have indicated that lesbian women reported higher desires and intentions for parenthood than gay men [3,41,91,92], thus confirming the findings of the international literature [34,93], other Italian studies [49,92] did not find significant differences between lesbian women and gay men. In the present study, lesbian women reported significantly greater motives to not have children compared to gay men.…”
Section: Discussionsupporting
confidence: 77%
“…Regarding motives for parenthood, research findings in the Italian LG population are mixed. While some studies have indicated that lesbian women reported higher desires and intentions for parenthood than gay men [3,41,91,92], thus confirming the findings of the international literature [34,93], other Italian studies [49,92] did not find significant differences between lesbian women and gay men. In the present study, lesbian women reported significantly greater motives to not have children compared to gay men.…”
Section: Discussionsupporting
confidence: 77%
“…Heterosexual and LGB people report valuing parenthood equally, believing that the associated rewards justify the work and costs involved (Riskind & Patterson, 2010). Regardless of gender composition, couples with parenting desires report the same motivations for wanting to have children (Santona et al, 2021). These include feelings of happiness, affection, fulfilment, positive benefits for the entire family, and a wish to live symbolically through one's children after death.…”
Section: Part 2: Lgb People's Desires and Expectations For Parenthoodmentioning
confidence: 99%
“…Gay men share similar reasons with their heterosexual counterparts for becoming, or not becoming, a father, such as a quest for life enrichment, expected positive changes from parenthood, continuity of the family line, and consideration of financial, emotional, and physical costs (Gato et al, 2020 ; Goldberg et al, 2012 ; Santona et al, 2022 ; van Houten et al, 2020 ). Even those who choose not to pursue parenthood may perceive having a child as desirable and valuable (Kranz et al, 2018 ; Shenkman, 2012 ).…”
Section: Introductionmentioning
confidence: 99%